2011
DOI: 10.1002/jmri.22696
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diffusion‐weighted MRI and MR volumetry in the evaluation of early treatment outcomes after preoperative chemoradiotherapy for locally advanced rectal cancer

Abstract: Purpose: To compare diffusion-weighted imaging (DWI) and magnetic resonance (MR) volumetry for predicting treatment outcomes of locally advanced rectal cancers with preoperative chemoradiotherapy (CRT). Materials and Methods:This prospective study was approved by our Institutional Review Board. Thirty-four patients underwent three MR examinations: pre-CRT (before CRT), early CRT (2 weeks after CRT initiation), and post-CRT (before surgery). The tumor apparent diffusion coefficient (ADC), ADC increase rate, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 22 publications
1
60
0
1
Order By: Relevance
“…A few authors advocate the use of bowel preparation based on rectal suppository laxatives [10,12,16]. Several studies have reported the use of intravenous administration of spasmolytic agents to reduce bowel peristalsis, which may be particularly useful at 3 T MR imaging [11][12][13]16,18].…”
Section: Rectal Dw-mr Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…A few authors advocate the use of bowel preparation based on rectal suppository laxatives [10,12,16]. Several studies have reported the use of intravenous administration of spasmolytic agents to reduce bowel peristalsis, which may be particularly useful at 3 T MR imaging [11][12][13]16,18].…”
Section: Rectal Dw-mr Imagingmentioning
confidence: 99%
“…Early publications concerning application of DW-MRI to rectal disease mainly dealt with evaluation of tumor response to treatment [3][4][5][6]. Since then, rectal DW-MRI has become a feasible option and several groups have confirmed early encouraging results in the area of rectal disease detection [7][8][9] or tumoral response evaluation [3,8,[10][11][12][13][14][15][16][17][18][19][20]. Recent guidelines for rectal cancer imaging even recommend DW-MRI as part of a standard MR imaging protocol for preoperative restaging of rectal cancers after neoadjuvant chemoradiotherapy (CRT) [21].…”
Section: Introductionmentioning
confidence: 99%
“…In multiple studies it was shown that T2-weighted (T2w) MRI tumor volume reduction was predictive for pathological response after neo-adjuvant therapy [5][6][7][8]. Besides, also several studies showed that functional MR imaging is helpful for response prediction after neo-adjuvant therapy.…”
mentioning
confidence: 99%
“…Lambregts et al (28) previously reported that the quantitative evaluation of the ADC may be used as a biomarker for the response to treatment. The diagnostic performance of the ADC with various cut-off values ranging between 1.2 and 1.4 x10 3 mm 2 /sec in RC has been reported to be equivalent to ~46-100% sensitivity and ~56-84% specificity (18,19,21,29). The value of DW-MRI as a predictive tool for assessing response to NA-CRT in patients with RC is currently poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that necrotic areas with high pretreatment ADC values may be less sensitive to CRT. However, several studies have produced contradictory results (29,30). Previously published data on the value of DW-MRI as a predictive tool for anticancer treatment responses in patients with RC are scarce and conflicting.…”
Section: Introductionmentioning
confidence: 99%